2021
DOI: 10.3389/fnut.2021.633807
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Fibre-Associated Foods and Texture Preferences in Relation to Weight Status Among 9–12 Years Old Children in 6 European Countries

Abstract: Plant foods, rich in fibre, can offer textures that children find difficult to orally manipulate, resulting in low preferences but are important for a healthy diet and prevention of overweight in children. Our aim was to investigate preferences for food texture, intake of fibre-associated foods and the relation to BMI. Three hundred thirty European children (9–12 years, 54% female) indicated their texture preferences using the Child-Food-Texture-Preference- Questionnaire (CFTPQ), and their parents responded on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 89 publications
0
12
0
Order By: Relevance
“…Food intake plays a critical role in the development of metabolic diseases. Recently, an investigation on European children from six different nations has highlighted that the consumption of fiber-rich foods does not meet present recommended daily intake guidelines [ 6 ]. The authors have found out a weak but significant correlation between an increase in BMI and a decrease in consumption frequency of wholegrain cereals and wholemeal products (bread, cereals, biscuits, pasta, rice).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food intake plays a critical role in the development of metabolic diseases. Recently, an investigation on European children from six different nations has highlighted that the consumption of fiber-rich foods does not meet present recommended daily intake guidelines [ 6 ]. The authors have found out a weak but significant correlation between an increase in BMI and a decrease in consumption frequency of wholegrain cereals and wholemeal products (bread, cereals, biscuits, pasta, rice).…”
Section: Introductionmentioning
confidence: 99%
“…The authors have found out a weak but significant correlation between an increase in BMI and a decrease in consumption frequency of wholegrain cereals and wholemeal products (bread, cereals, biscuits, pasta, rice). Furthermore, adopting the consumption of high-fiber foods in early childhood can delay the initiation of impaired condition [ 6 , 7 ]. These results are mostly driven by Italy (lower cereals consumption frequency).…”
Section: Introductionmentioning
confidence: 99%
“…Out of the 100 participating preadolescents (11–12 years), 40% were living with overweight or obesity, categorized by BMI for age percentiles. This is a very high proportion compared to other investigations, which reported 19% [ 37 ] and 31% [ 38 ] of children living with overweight or obesity. The children included in the other examinations were partly younger (9 to 12 years of age), and the prevalence might be lower in younger ones here.…”
Section: Discussionmentioning
confidence: 57%
“…In particular, dietary factors are importantly associated with childhood obesity ( 10 ) and the prevalence rates of diet-related diseases, such as obesity and diabetes in children and adolescents, push for the right priority to healthy diets ( 8 , 9 , 11 ). Many children, instead of a diet rich in fruits and vegetables, choose snacks with saturated trans fats and sugar ( 12 ), which lead to a higher energy intake ( 13 ) and consequently to overweight/obesity ( 12 , 14 , 15 ). The assumption of harmful behaviors, such as eating unhealthy foods, during the time spent in a sedentary lifestyle, has been shown to exacerbate the capacity to maintain an adequate body weight in children by creating a vicious cycle ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%